2024 Clinical practice guidelines for Hypertension in adults - Kobalava, Zh. D.; Konradi, A. O.; Nedogoda, S. V.; Shlyakhto, E. V.; Arutyunov, G. P.; Baranova, E. I.; Barbarash, O. L.; Bobkova, N. V.; Boytsov, S. A.; Bubnova, M. G.; Vavilova, T. V.; Villevalde, S. V.; et al. (Rossiĭskiĭ kardiologicheskiĭ zhurnal, 2024)
The Russian Society of Cardiology (RKO) With the participation of: Russian Scientific Medical Society of Internal Medicine (RSMSIM) Approved by the Research and Practical Council of the Ministry of Health of the Russian Federation (12.09.2024)